Peran Moderasi Prio Opinion Terhadap Hubungan Prediksi Kebangkrutan Dengan Opini Audit Going Concern - Rudi Zulfikar; Anggie Lestari; Nana Nofianti; Kurniasih Dwi Astuti (Jurnal Ekonomi, 2022)
This study examines the effect of ongoing bankruptcy predictions on audit opinions with previous opinions as moderating variables in the manufacturing industry listed on the Indonesia Stock Exchange during the 2014-2019 period. Measurement of bankruptcy prediction variables using Altman's. Z-Score. The sampling technique used in this research is the purposive sampling method. In addition, the regression analysis the model used to examine the interaction of bankruptcy prediction variables with previous opinions uses Moderated. Regression Analysis (MRA). The test results prove that the bankruptcy prediction as measured by Altman's Z-Score has a negative effect on ongoing concern audit opinion. Other evidence confirms that the prior opinion variable as measured by the dummy variable reduces the relationship between bankruptcy prediction and going concern audit opinion.